Editionsgeschichtliche Aspekte zu Alfred Döblins Romantetralogie "November 1918" - Jäkel, Siegfried (Studia Germanica Posnaniensia, 2018)
Starting from an editorial historical sketch of the edition of revolutionary novel „November 1918“ by Alfred Döblin, the explanation of difficulties which the author had met having tried to publish his work in the unabridged version of the World War, as well as postwar one, was to be found. These difliculties explain also the fact that in Germanistic research on Döblin's work this novel has so far been omitted or very little place was sacrificed to it. The real hero of the novel are the events of the year 1918. They are a surprise for the figures appearing in the novel and they occur above the figures and against their plans. The novel-tetralogy, which consists of almost 2000 pages, is constructed as a mosaic, consisting of many independent stones (novels). Only one figure - Dr. Friedrich Becker, classical philologist, lieutnant from the Ist World War does disappear from the stage of the novel from the beginning to the end. It seems that in his tetralogy Döblin wanted to draw our attention that both idealists and revolutionists are sentenced to defect facing so called „norms“.